The Consistency of Islamic and Medical Perspectives in the Control of the COVID-19 Pandemic - Mossad Abdelhak Shaban Mohamed; HansVan Rosternberghe; Noraida Ramli; Nor Rosidah Ibrahim; Manar Mossad; Taufiq Hidayat (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 03-2021) [August 2021]